2020
DOI: 10.1111/bph.15153
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant thrombomodulin protects against LPS‐induced acute respiratory distress syndrome via preservation of pulmonary endothelial glycocalyx

Abstract: Background and Purpose Disruption of the endothelial glycocalyx is causally related to microvascular endothelial dysfunction, a characteristic of sepsis‐induced acute respiratory distress syndrome (ARDS). Recombinant human thrombomodulin (rhTM) attenuates vascular endothelial injuries, but the underlying mechanism remains elusive. Here, we investigated the structural basis and molecular mechanisms of rhTM effects on vascular endothelial injury in a model of sepsis. Experimental Approach LPS (20 mg·kg−1) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…58 Although further experiments are required to understand how rhTM affects endothelial glycocalyx biosynthesis, it has been suggested that there is an interaction between thrombomodulin and endothelial glycocalyx thrombomodulin at least. 54…”
Section: What C and Idate S For Endothelial G Lyco C Aly X Protec Tmentioning
confidence: 99%
See 4 more Smart Citations
“…58 Although further experiments are required to understand how rhTM affects endothelial glycocalyx biosynthesis, it has been suggested that there is an interaction between thrombomodulin and endothelial glycocalyx thrombomodulin at least. 54…”
Section: What C and Idate S For Endothelial G Lyco C Aly X Protec Tmentioning
confidence: 99%
“…A very recent report revealed that recombinant human thrombomodulin (rhTM) protects endothelial glycocalyx from lipopolysaccharide (LPS)-induced pulmonary injury. 54 This mechanism may be involved with not only the reduction of the damage associated with inflammation but also the acceleration of the biosynthesis of the glycocalyx itself. Thrombomodulin exists at the luminal surface of all vessel segments and especially at venular endothelial cell junctions, 34 binds to thrombin to inhibit its pro-coagulant activity, and promotes anticoagulant protein C activation.…”
Section: What C and Idate S For Endothelial G Lyco C Aly X Protec Tmentioning
confidence: 99%
See 3 more Smart Citations